The inFlow intraurethral valve-pump for women with detrusor underactivity: A summary of peer-reviewed literature. (4th July 2022) - Hartigan, Siobhan M.; Dmochowski, Roger R.
Abstract : Context: Detrusor underactivity (DUA) in women can result in urinary retention and the need for chronic bladder drainage management. Without a cure for urinary retention due to DUA, treatment options are focused on effective bladder drainage most often by intermittent or continuous catheter drainage. The inFlow intraurethral valve pump was FDA approved for use in women with this condition in 2014. Methods: Using a literature search, this clinical review sought to explore the epidemiology and commonly used treatment options for women with DUA and critically examine all available studies of the inFlow urinary prosthesis. Results: Due to a lack of effective treatments to improve detrusor function, DUA is generally considered incurable and there are limited treatment options which mostly focus on effective bladder drainage. The inFlow urinary prosthesis is a unique technology which utilizes a nonsurgically inserted urethral device for females to assist with bladder drainage due to DUA. The inFlow urinary prosthesis has been used in Europe and elsewhere for 20 years and is the subject of seven peer-reviewed clinical studies. For those that tolerate the device (about half), the inFlow urinary prosthesis has a low infection rate and side effect profile, is easy to use, and can normalize urination by returning autonomy to patients and thus improve their quality of life. Conclusion: There is no cure for women with DUA. Bladder drainage can be managed by intermittent or continuous catheterization. Appropriately selected women interested in an alternative to catheterization may be offered an on-device trial of the inFlow urinary prosthesis.